A review of a strategic roadmapping exercise to advance clinical translation of photoacoustic imaging: From current barriers to future adoption - Hisham Assi; Rui Cao; Madhura Castelino; Ben Cox; Fiona J. Gilbert; Janek Gröhl; Kurinchi Gurusamy; Lina Hacker; Aoife M. Ivory; James Joseph; Ferdinand Knieling; Martin J. Leahy; et al. (Photoacoustics, 2023)
Photoacoustic imaging (PAI), also referred to as optoacoustic imaging, has shown promise in early-stage clinical trials in a range of applications from inflammatory diseases to cancer. While the first PAI systems have recently received regulatory approvals, successful adoption of PAI technology into healthcare systems for clinical decision making must still overcome a range of barriers, from education and training to data acquisition and interpretation. The International Photoacoustic Standardisation Consortium (IPASC) undertook an community exercise in 2022 to identify and understand these barriers, then develop a roadmap of strategic plans to address them. Here, we outline the nature and scope of the barriers that were identified, along with short-, medium- and long-term community efforts required to overcome them, both within and beyond the IPASC group.